Tương tác giữa keo nano bạc với ion thuỷ ngân (II) và sự thay đổi tính chất cộng hưởng plasmon bề mặt của nó - Trung, Nguyễn Bá (Vietnam Journal of Chemistry, 2016)
Localized surface plasmon resonance of nanoparticles, especially AuNP and AgNP, has been extensively exploited in many applications related to chemical and biological sensing. AgNP shows the best dominant plasmon resonance characteristic compared to other nano metals. Thereforce, it is quite sensitive to changes in the size and shape of nano particles, as well as external medium on the particle surface. This is the basis for exploiting this nature in the development of sensor systems. This work presents a chemical method to prepare AgNP colloidal systems which was then exammined the physical characteristics through physical analyzes, including surface plasmon resonance characteristic, X-ray diffraction analysis (XRD) and TEM. Experimental results showed that the color of AgNP solution was changed, accompanying with a decrease in size of AgNP and a blue shift in absorption wavelength in the presence of Hg2+, due to the chemical reaction between Hg2+ and AgNPs. The positive results of this work can be applied to the development of sensors based on the color change for quick screening Hg2+ in water samples. Keywords. Silver nanoparticle, plasmon resonance, sensor, mercury, mercury analysis in water sample.